Integrating smoking cessation into routine care in hospitals—a randomized controlled trial. (13th January 2016) - Thomas, D.; Abramson, M. J.; Bonevski, B.; Taylor, S.; Poole, S. G.; Paul, E.; Weeks, G. R.; Dooley, M. J.; George, J.
Abstract: Aims: To evaluate the effectiveness of a pharmacist‐led multi‐component smoking cessation programme (GIVE UP FOR GOOD) compared with usual care in hospitalized smokers. Design: Randomized, assessor‐blinded, parallel‐group trial. Setting: Three tertiary public hospitals in Australia. Participants: A total of 600 adult in‐patient smokers [mean ± standard deviation (SD), age 51 ± 14 years; 64% male] available for 12 months follow‐up. Interventions: Multi‐component hospital pharmacist‐led behavioural counselling and/or pharmacotherapy provided during hospital stay, on discharge and 1 month post‐discharge, with further support involving community health professionals ( n = 300). Usual care comprised routine care provided by hospitals ( n = 300). Measurements: Two primary end‐points were tested using intention‐to‐treat analysis: carbon monoxide (CO)‐validated 1‐month sustained abstinence at 6‐month follow‐up and verified 6‐month sustained abstinence at 12‐month follow‐up. Smoking status and pharmacotherapy usage were assessed at baseline, discharge, 1, 6 and 12 months. Findings: Sustained abstinence rates for intervention and control groups were not significantly different at both 6 months [11.6% (34 of 294) versus 12.6% (37 of 294); odds ratio (OR) = 0.91, 95% confidence interval (CI) = 0.55–1.50] and 12 months [11.6% (34 of 292) versus 11.2% (33 of 294); OR = 1.04, 95% CI = 0.63–1.73]. Secondary end‐points, self‐reported continuous abstinence at 6 and 12 months, also agreed with the primary end‐points. Use of pharmacotherapy was higher in the intervention group, both during hospital stay [52.3% (157 of 300) versus 42.7% (128 of 300); P = 0.016] and after discharge [59.6% (174 of 292) versus 43.5% (128 of 294); P < 0.001]. Conclusions: A pharmacist‐led multi‐component smoking cessation intervention provided during hospital stay did not improve sustained abstinence rates at either 6 or 12 months compared with routine hospital care.